Proteomic characterization and comparison of Malaysian Tropidolaemus wagleri and Cryptelytrops purpureomaculatus venom using shotgun-proteomics - Zainal Abidin, Syafiq Asnawi; Rajadurai, Pathmanathan; Chowdhury, Md Ezharul Hoque; Ahmad Rusmili, Muhamad Rusdi; Othman, Iekhsan; Naidu, Rakesh (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Tropidolaemus wagleri and Cryptelytrops purpureomaculatus are venomous pit viper species commonly found in Malaysia. Tandem mass spectrometry analysis of the crude venoms has detected different proteins in T. wagleri and C.purpureomaculatus. They were classified into 13 venom protein families consisting of enzymatic and nonenzymatic proteins. Enzymatic families detected in T. wagleri and C. purpureomaculatus venom were snake venom metalloproteinase, phospholipase A2, L-amino acid oxidase, serine proteases, 50-nucleotidase, phosphodiesterase, and phospholipase B. In addition, glutaminyl cyclotransferase was detected in C. purpureomaculatus. C-type lectin-like proteins were common nonenzymatic components in both species. Waglerin was present and unique to T. wagleri—it was not in C. purpureomaculatus venom. In contrast, cysteine-rich secretory protein,bradykinin-potentiating peptide, and C-type natriuretic peptide were present in C. purpureomaculatus venom. Composition of the venom proteome of T. wagleri and C. purpureomaculatus provides useful information to guide production of effective antivenom and identification of proteins with potential therapeutic applications.